Using a central Vehicle Holding Compound (VHC) in an open pipeline automotive order fulfilment system: a simulation study - MacCarthy, Bart L.; Ovutmen, Tamer (Elsevier, 2015)
Satisfying requests for specific vehicle variants in a timely manner may increase profit margins for the automotive producer and automotive dealers and may reduce the need to incentivise customers financially to make a purchase. Open pipeline order fulfilment systems have emerged in the automotive sector to allow dealers to fulfil a customer in a number of ways. Not only can a dealer search its own stock for a suitable match to a customer’s requested vehicle specification, the dealer can also search for a suitable vehicle in the planning, assembly or distribution pipeline. If a suitable match cannot be found, the dealer can submit a specific Build-to-Order request to the producer. This study examines the impact of adding a central vehicle holding compound (VHC) in such a system. Any dealer can search for a suitable vehicle match in the VHC. A simulation study of a real automotive fulfilment system is conducted to examine the effects on order fulfilment performance of establishing a VHC in a specific market. The simulation model incorporates important features that affect the management and control of the fulfilment system. The study shows that establishing a VHC in an open pipeline system has a significant effect on the level of use of each fulfilment mechanism and on fulfilment performance. A VHC results in significant reductions in lead time but can increase the total stock level in the system if the VHC operating conditions are not determined carefully. The insights and implications of the findings are discussed in detail. They are valuable in providing a base line to consider investment in a VHC and to decide the most appropriate operating policies.